Remission in systemic lupus erythematosus: testing different definitions in a large multicentre cohort. Issue 7 (22nd April 2020) - Saccon, Francesca; Zen, Margherita; Gatto, Mariele; Margiotta, Domenico Paolo Emanuele; Afeltra, Antonella; Ceccarelli, Fulvia; Conti, Fabrizio; Bortoluzzi, Alessandra; Govoni, Marcello; Frontini, Giulia; Moroni, Gabriella; Dall'Ara, Francesca; et al.
Abstract : Objectives: Remission in systemic lupus erythematosus (SLE) is defined through a combination of 'clinical SLE Disease Activity Index (cSLEDAI)=0', 'physician's global assessment (PGA) <0.5' and 'prednisone (PDN) ≤5 mg/day'. We investigated the performance of these items, alone or in combination, in defining remission and in predicting SLICC/ACR Damage Index. Methods: We tested seven potential definitions of remission in SLE patients followed-up for ≥5 years: PDN ≤5 mg/day; PGA <0.5; cSLEDAI=0; PGA <0.5 plus PDN ≤5 mg/day; cSLEDAI=0 plus PGA <0.5; cSLEDAI=0 plus PDN ≤5 mg/day; cSLEDAI=0 plus PDN ≤5 mg/day plus PGA <0.5. The effect of these definitions on damage was evaluated by Poisson regression analysis; the best performance was identified as the lowest Akaike and Bayesian information criterion (AIC and BIC). Positive and negative predictive values in identifying no damage increase were calculated. Results: We included 646 patients (mean±SD disease duration 9.2±6.9 years). At multivariate analysis, ≥2 consecutive year remission according to all definitions protected against damage (OR, 95% CI: PGA <0.5 0.631, 0.444 to 0.896; cSLEDAI=0 0.531, 0.371 to 0.759; PGA <0.5 plus PDN ≤5 mg/day 0.554, 0.381 to 0.805; cSLEDAI=0 plus PGA <0.5 0.574, 0.400 to 0.826; cSLEDAI=0 plus PDN ≤5 mg/day 0.543, 0.376 to 0.785; cSLEDAI=0 plus PDN ≤5 mg/day plus PGA <0.5 0.532, 0.363 to 0.781, p<0.01 for all), except PDN ≤5 mg/day, which required four consecutive years (OR 0.534, 95% CI 0.325 to 0.877, p=0.013). Positive and negative predictive values were similar; however, cSLEDAI=0 showed the best performance (AIC 1082.90, BIC 1109.72, p<0.0001). Adding PGA <0.5 and/or PDN ≤5 mg/day to cSLEDAI=0 decreased remission duration (−1.8 and −1.5 year/patient, respectively) without increasing cSLEDAI=0 performance in predicting damage accrual. Conclusions: cSLEDAI=0 is the most attainable definition of remission, while displaying the best performance in predicting damage progression in the short-to-mid-term follow-up.